(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The research aims to identify the role of kindergarten theater in enhancing children’s awareness of disasters from the teachers’ perspective. The researcher used the descriptive approach and designed a questionnaire consisting of (26) statements, wich was administered to a sample of (168) kindergarten teachers. The research results showed that the role of kindergarten theater in enhancing children’s awareness of disasters, from the perspective of kindergarten teachers in Lattakia City, was moderate. The results also showed no statistically significant differences between the average scores of the sample on the questionnaire regarding the role of kindergarten theater in enhancing children’s awareness of disasters, based on the variable of years of experience. according to the experience. however, there were statistically significant differences between their average scores based on the varible educational qualification, favoring of those with a university degree and a teaching diploma. Additionally , there was a statistically significant difference between their average scores based on the variable of training courses in the field of children’s theater, favoring teachers who had attended training courses.the researcher suggested that the ministry of education prepare training courses to train teachers on how to use kindergarten theater.